An assessment of natural and anthropogenic trace elements in the atmospheric deposition during 1776–2004 A.D. using the Miaoergou ice core, eastern Tien Shan, China. (15th January 2020) - Zou, Xiang; Hou, Shugui; Wu, Shuangye; Zhang, Wangbin; Liu, Ke; Yu, Jinhai; Liu, Yaping; Pang, Hongxi
Abstract: An annually resolved trace element (TE) record is established for V, Mn, Co, Ni, Cu, As, Rb, Sr, Mo, Sn, Sb, Ba, Tl, Bi, Th, U, Cr, and Pb from the Miaoergou ice core, eastern Tien Shan, China, covering the period 1776–2004 A.D.. Using this record, we examined the continuous changes of atmospheric TE compositions and identified their natural and anthropogenic sources based on the analysis of their enrichment factors (EF) and excess (Ex) concentrations. First, the record shows high concentrations of crustal elements during the periods of 1787–1813 A.D., 1825–1887 A.D., 1941–1978 A.D., likely originated from the surrounding deserts, especially the Taklimakan Desert. Second, similar to other natural archive records from the Northern Hemisphere, the data show sporadic Ex concentrations of Pb, Sn, Cu, Tl before the 1950s, likely related to the coal combustion and non-ferrous production/smelting in the European countries since the Industrial Revolution. Finally, the record reveals significant anthropogenic contribution to concentrations of Pb, Sn, Cu, Sb, As, Bi, and Tl in the second half of the 20th century. The Ex concentration of these elements started to increase sharply in the 1950s, reached the maximum levels in the 1970s–1980s, subsequently declined in the early 1990s, and finally rose again in the late 1990s. The temporal TE trends could reflect the industrial and agricultural development in the possible source regions (e.g., the former Soviet Union). Therefore, our high-resolution record of atmospheric TEs provides a valuable historical perspective on air pollution emissions in these regions surrounding Miaoergou since the Industrial Revolution. Highlights: First high-resolution multi-century trace element record from Miaoergou Glacier. An assessment of trace elements in the atmospheric deposition. The records reflect air pollution emissions since the Industrial Revolution.